Preferential Lineage-Specific Differentiation of Osteoblast-Derived Induced Pluripotent Stem Cells into Osteoprogenitors - Casey L. Roberts; Silvia S. Chen; Angela C. Murchison; Rebecca A. Ogle; Michael P. Francis; Roy C. Ogle; Patrick C. Sachs (Hindawi Limited, 2017)
While induced pluripotent stem cells (iPSCs) hold great clinical promise, one hurdle that remains is the existence of a parental germ-layer memory in reprogrammed cells leading to preferential differentiation fates. While it is problematic for generating cells vastly different from the reprogrammed cells' origins, it could be advantageous for the reliable generation of germ-layer specific cell types for future therapeutic use. Here we use human osteoblast-derived iPSCs (hOB-iPSCs) to generate induced osteoprogenitors (iOPs). Osteoblasts were successfully reprogrammed and demonstrated by endogenous upregulation of Oct4, Sox2, Nanog, TRA-1-81, TRA-16-1, SSEA3, and confirmatory hPSC Scorecard Algorithmic Assessment. The hOB-iPSCs formed embryoid bodies with cells of ectoderm and mesoderm but have low capacity to form endodermal cells. Differentiation into osteoprogenitors occurred within only 2-6 days, with a population doubling rate of less than 24 hrs; however, hOB-iPSC derived osteoprogenitors were only able to form osteogenic and chondrogenic cells but not adipogenic cells. Consistent with this, hOB-iOPs were found to have higher methylation of PPARγ but similar levels of methylation on the RUNX2 promoter. These data demonstrate that iPSCs can be generated from human osteoblasts, but variant methylation patterns affect their differentiation capacities. Therefore, epigenetic memory can be exploited for efficient generation of clinically relevant quantities of osteoprogenitor cells.